CD36 is involved in oleic acid detection by the murine olfactory system - Oberland, Sonja; Ackels, Tobias; Gaab, Stefanie; Pelz, Thomas; Spehr, Jennifer; Spehr, Marc; Neuhaus, Eva M. (Frontiers in Cellular Neuroscience, 2015)
Olfactory signals influence food intake in a variety of species. To maximize the chances of finding a source of calories, an animal’s preference for fatty foods and triglycerides already becomes apparent during olfactory food search behavior. However, the molecular identity of both receptors and ligands mediating olfactory-dependent fatty acid recognition are, so far, undescribed. We here describe that a subset of olfactory sensory neurons expresses the fatty acid receptor CD36 and demonstrate a receptor-like localization of CD36 in olfactory cilia by STED microscopy. CD36-positive olfactory neurons share olfaction-specific transduction elements and project to numerous glomeruli in the ventral olfactory bulb. In accordance with the described roles of CD36 as fatty acid receptor or co-receptor in other sensory systems, the number of olfactory neurons responding to oleic acid, a major milk component, in Ca2+ imaging experiments is drastically reduced in young CD36 knock-out mice. Strikingly, we also observe marked age-dependent changes in CD36 localization, which is prominently present in the ciliary compartment only during the suckling period. Our results support the involvement of CD36 in fatty acid detection by the mammalian olfactory system.